From Homer to Solon : Continuity and Change in Archaic Greece - Canevaro, Mirko; Bernhardt, Johannes C. (Mnemosyne, Supplements, 2022)
The study of Archaic Greece has undergone a fundamental transformation in recent decades. Whereas studies up to the 1980s had favoured narratives that converged on the more tangible reality of the Classical period and emphasized radical change, the increase in archaeological data and the cultural turn have led to an emphasis on long-term developments and continuities. After an introduction to the state of research, the volume offers a wide range of studies under the headings "Approaches on early-Archaic Greece," "Citizens and Citizen-States," and "Leaders and Reformers" ranging from Homer to Solon and circling around the central problem of continuity and change in Archaic Greece.